2014
DOI: 10.1097/paf.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death From Ruptured Choroid Plexus Arteriovenous Malformation

Abstract: Brain vascular malformations are recognized as having potential to produce hemorrhage, but leading to sudden death in children is uncommon. Arteriovenous malformations may be situated in any region of the brain, but very rarely, they can be restricted to the choroid plexus. We report here a rare case of sudden death in a child, caused by a ruptured vascular malformation with an unusual location, which was not identified grossly but only on histological examination. The size and the location of the lesion, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…PHH is also a common cause of hydrocephalus in adults 14,18,19 , in whom the condition is often associated with intraventricular haemorrhage resulting from hypertension, aneurysm rupture, or traumatic brain injury. 20 PIH is the most common cause of pediatric hydrocephalus worldwide 5 and is most prevalent in Africa, Latin America and Southeast Asia 8 . As mentioned above, in resource-poor countries, PIH is more common that PHH.…”
Section: Global Epidemiology Of Pih and Phhmentioning
confidence: 99%
“…PHH is also a common cause of hydrocephalus in adults 14,18,19 , in whom the condition is often associated with intraventricular haemorrhage resulting from hypertension, aneurysm rupture, or traumatic brain injury. 20 PIH is the most common cause of pediatric hydrocephalus worldwide 5 and is most prevalent in Africa, Latin America and Southeast Asia 8 . As mentioned above, in resource-poor countries, PIH is more common that PHH.…”
Section: Global Epidemiology Of Pih and Phhmentioning
confidence: 99%
“…A particular case report showed a sudden death in a kid, caused by a broken vascular malformation with an uncommon site, not recognized macroscopically but only on histological investigation [ 27 ]. In this case, an MPCT scan did not show the AVM, highlighting the crucial role of autopsy in this kind of death.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular malformations constitute one of the causes of intracerebral hemorrhage among others including brain neoplasms, coagulopathies, and cerebral and venous sinus thrombosis [6]. Arteriovenous malformations (AVMs) of the brain are abnormal vascular anomalies in which a connection exists between the feeding arteries and draining veins of the brain linked by an interspersed abnormal intervening capillary bed -known as a central nidus [7][8]. Clinically, brain AVMs are a well-known cause of death, mostly due to the resulting intracerebral hemorrhage; however; they can remain asymptomatic for a very long time [8].…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…In the pediatric age, ruptured AVMs are considered a rare cause of sudden unexpected death. Cioca et al report an exceedingly rare case of sudden non-traumatic death in a previously healthy nine-year-old boy due to a ruptured AVM of the choroid plexus of the fourth ventricle [7]. Another case by Racette et al reported the sudden non-traumatic death of a 14-year-old girl who was previously well, except for mild asthma [9].…”
Section: Vascular Malformationsmentioning
confidence: 99%
See 1 more Smart Citation